2024
DOI: 10.17305/bb.2024.10236
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnostic value of contrast-enhanced ultrasound combined with microflow imaging in benign and malignant renal tumors: A retrospective cohort study

Xiufeng Kuang,
Huiyang Wang,
Weilu Chai
et al.

Abstract: This study aims to evaluate the clinical diagnostic value of contrast-enhanced ultrasound combined with microflow imaging (CEUS-MFI) in the differential diagnosis of benign and malignant renal tumors. All patients underwent CEUS, MFI, color doppler flow imaging (CDFI), and CEUS-MFI. The efficacies of these different diagnostic modalities in diagnosing benign and malignant renal tumors were evaluated by Kappa consistency test and the receiver operating characteristic (ROC) curve, with pathological findings serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Additionally, CEUS was better in the examination of masses with the largest diameter less than 2 cm, deep location, or dorsal renal masses. Furthermore, another study by Kuang et al inferred that CEUS-MFI had the highest consistency with pathological diagnosis (Kappa = 0.808) in comparison to MFI alone [55]. Overall, it can be concluded that CEUS can detect more blood flow signals than SMI.…”
Section: Ceus Vs Other Diagnostic Imaging Methodsmentioning
confidence: 89%
“…Additionally, CEUS was better in the examination of masses with the largest diameter less than 2 cm, deep location, or dorsal renal masses. Furthermore, another study by Kuang et al inferred that CEUS-MFI had the highest consistency with pathological diagnosis (Kappa = 0.808) in comparison to MFI alone [55]. Overall, it can be concluded that CEUS can detect more blood flow signals than SMI.…”
Section: Ceus Vs Other Diagnostic Imaging Methodsmentioning
confidence: 89%